A Holistic Control System Framework for Managing Complex Multistream Crude Processing in Floating Production Units - Andrew Tochukwu Ofoedu; Joshua Emeka Ozor; Oludayo Sofoluwe; Dazok Donald Jambol (International Journal of Scientific Research in Civil Engineering, 2023)
Floating Production Units (FPUs), such as Floating Production Storage and Offloading (FPSO) vessels, are increasingly deployed in deepwater and marginal fields to manage complex and variable crude oil streams. These facilities handle multistream crude processing involving varying compositions, pressure-temperature regimes, and dynamic interactions between gas, oil, water, and solid phases. Traditional control architectures in such environments often struggle with process variability, nonlinear dynamics, and operational unpredictability, leading to inefficiencies, frequent manual interventions, and increased downtime. To address these challenges, this proposes a holistic control system framework tailored for managing complex multistream crude processing in FPUs. The proposed framework integrates modular control layers, advanced process monitoring, real-time optimization, and predictive analytics to deliver adaptive, resilient, and efficient operations. Key components include a multivariable control core, dynamic process modeling using hybrid first-principles and data-driven techniques, and a supervisory layer that incorporates machine learning for anomaly detection, fault prediction, and performance enhancement. Additionally, the framework enables seamless coordination between subsystems such as separation, compression, dehydration, and stabilization units. By leveraging edge computing, IoT-enabled sensor networks, and digital twin technologies, the framework provides real-time visibility and control across the entire crude processing train. A closed-loop feedback structure facilitates automated decision-making, while operator-in-the-loop capabilities ensure situational awareness and accountability. This integrated approach enhances process stability, reduces energy consumption, improves throughput, and minimizes unplanned shutdowns. This also outlines implementation strategies and discusses potential performance gains using simulated scenarios based on actual field data. Overall, the proposed holistic control framework represents a significant advancement toward smart, autonomous offshore processing systems. It provides a scalable solution for next-generation FPUs aiming to maximize resource recovery, ensure process integrity, and adapt to the operational complexity inherent in modern offshore environments.